2007
DOI: 10.2174/156652307782151524
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Immune Modulation

Abstract: Successful gene therapy protocols rely on the hypo-responsiveness of the immune system to transgene products generated from gene transfer vectors. In order to prevent cytotoxic lymphocyte or antibody formation induced by transgene expression, various strategies derived from recent advances in immune tolerance induction protocols have been tested in gene therapy model systems. Current immunosuppressive drugs were used to nonspecifically target T-cell activation, clonal expansion, and differentiation into effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 121 publications
(153 reference statements)
0
9
0
Order By: Relevance
“…Some of these approaches are described below. In the companion review, Carol H. Miao also discussed some immunointervention strategies, which could enable long-term transgene expression [Miao, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these approaches are described below. In the companion review, Carol H. Miao also discussed some immunointervention strategies, which could enable long-term transgene expression [Miao, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that immune responses against vectors or transgene products can become major obstacles for successful application of gene therapy. [1][2][3] Hemophilia A, a congenital bleeding disorder caused by a monogenic defect of coagulation factor VIII (FVIII), is an ideal candidate for the successful application of somatic cell gene therapy. Previous preclinical and clinical trials demonstrated that viral and nonviral gene transfer of FVIII [4][5][6][7][8][9] often results in transient gene expression in the absence of immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, safe and effective means to induce tolerance and prevent and/or modulate the transgene-specific immune responses after gene therapy need to be developed. 22 Limited success has been achieved to induce tolerance against transgene product on prolonged exposure to antigens, including mucosal administration of FVIII-C2 domain, 23 B-cell gene therapy, 24 or hepatic gene transfer. 25 However, in most cases tolerance was established in only a fraction of the treated animals.…”
Section: Introductionmentioning
confidence: 99%